Integration of Refugees on the Danish Labor Market - Bredgaard, Thomas; Thomsen, Trine Lund (Nordic Journal of Working Life Studies, 2018)
The unprecedented inflow of refugees in the Nordic countries since 2014 has accentuated debates about the effectiveness of the Nordic models and their labor market integration programs. The ‘refugee crisis’ opened a window of opportunity in which some Nordic countries reformed their policy framework to promote faster and more effective labor market integration of refugees. Denmark is celebrated for its well-functioning flexicurity labor market, but has not been particularly successful in integrating nonwestern migrants and refugees in the labor market. We examine barriers on the supply-side, the demand-side, and in the matching process of the labor market to better understand the labor market performance of refugees. Subsequently, we analyze the new Danish labor market integration programs and discuss preliminary implementation results. Although it is too early to make any final judgments of the outcomes, there are indications of positive changes in implementation and results, while important integration issues remain unresolved.